Wanted - Gray, Shelley Shepard (New York : Avon Inspire, 2009)
Hiding the truth about her feelings for widower Jonathan because of her youthful indiscretions outside of their Amish community, Katie receives a note that threatens to expose her, forcing her to evaluate her understanding about the nature of forgiveness.